Quality of life of patients with lower jaw benign tumor post resection and mandibular reconstruction - Arindra, Pingky Krisna; Sejati, Bramasto Purbo; Rahardjo, Rahardjo (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
The quality of life of patients becomes an essential part of the success of an intervention since it is used as an outcome measure. Mandible resection will cause discontinuities that can degrade the quality of life of patients. Extensive resectionand reconstruction will affect the quality of life of patients after resection and reconstruction surgery as compared with that before the surgery. On this basis, cross-sectional study was conducted among 27 patients suffering from benignmandibular tumors undergoing surgical procedure of marginal resection, segmental resection, or hemimandibulectomy at Dr. Sardjito genral hospital in 2010-2015. Quality of life of patients after mandibular resection and reconstruction was measured with modified oral health impact profile (OHIP-14). An assessment of the quality of life before and after surgery was based on gender and type of reconstruction and it was analyzed using t-test and one-way ANOVA. It was revealed that the quality of life of patients with benign tumors increased significantly (p=0,000), and that gender differences did not significantly affect the improved quality of life (p=0.433). The mean score of patient’s quality of life was highest on the type of marginal resection (mean value =14.50), and the lowest was on segmental resection (mean value=7.50), but the type of resection did not significantly influence the improved quality of life (p=0.152). Resection and reconstruction procedures under taken by Oral and Maxillofacial Surgeon at Dr. Sardjito general hospital can improve the quality of life of patients with benign tumors of the lower jaw.